The Problematic Issues for Starting a Business Faced by Business Graduates (Global Journal of Management and Business Research, 2020)
The objective of this research paper is to investigate the process and obstacles that new business start-ups face. The identification of entry barriers is critical because the removal of these restrictions and the development of small businesses may lead to the development of the country, as small businesses are the lifeblood of our economy. These serve as engines for developing countries such as Sri Lanka, which is now a lower-middle emerging market. The objective of this research is to identify and investigate the most fundamental issues that new businesses encounter. Our country's government aims to reduce unemployment, with the higher unemployment rate among fresh graduates. For more than three decades, graduate unemployment has been a major issue in Sri Lanka. We investigated the challenges, difficulties, and obstacles that graduating entrepreneurs have faced or would face while launching a startup through this study. For this study, 184 newly graduated business faculty students from private tertiary educational institute provided data.
Keywords: business graduates; entrepreneurialism; start-up barriers; youth unemployment